Patient Safety Attitudes Among Intensive Care Unit Nurses in an Indonesian Islamic Hospital: A Mixed-Methods Study - Tri Sutopo; Arlina Dewi (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Patient safety culture plays a crucial role in intensive care units (ICUs), where nurses play a central role in ensuring safe and quality care. Evaluation of patient safety attitudes in nurses is important to reduce medical errors and improve service quality. This study aims to evaluate patient safety attitudes in nurses in the ICU of an Islamic hospital and propose a strategy for improvement based on the Theory of Planned Behavior (TPB). Mixed-methods with a sequential explanatory model approach, using the Safety Attitudes Questionnaire (SAQ-INA). Quantitative data from ICU nurses were complemented by qualitative interviews, analyzed using the TPB framework. The number of respondents in this study was 14 respondents from both quantitative and qualitative research. ICU nurses showed a positive attitude with high scores on the teamwork climate (82.7%), safety climate (76.3%), and job satisfaction (90.4%). However, low scores on stress recognition (61.6%), unit management perception (66.8%), hospital management (68.6%), and working conditions (74.1%) indicate challenges such as high workload, staff shortages, and lack of management support. The qualitative findings emphasize the need for non-punitive reporting and collaboration between professions. ICU nurses are strongly committed to patient safety, but stress and resource limitations hinder them. Recommendations include stress management training, non-punitive reporting systems, management engagement, and resource optimization to strengthen patient safety attitudes Keywords: Patient Safety Attitudes, ICU Nurses, Safety Attitudes Questionnaire, Theory of Planned Behavior